MEMENANGKAN PERSAINGAN PERGURUAN TINGGI ISLAM SWASTA (Studi Komunikasi Pemasaran STAI Ahsanta Jambi) - Fridiyanto, Muhammad Rafi’i, Miftahul Khairani (Al-Balagh : Jurnal Komunikasi Islam, 2020)
Abstract: this study investigated the marketing communication strategy with a specific focus on private Islamic higher education. The research design adopted for the research was a qualitative method with a case study approach. The findings revealed that STAI Ahsanta apllied multi strategies in marketing their program, such as: digital marketing, convensional marketing, cost leadership and empower their staffs to involve in promoting the institution. Additionally, our findings suggested solutions to overcome the problems of marketing in disruptive era through maximizing multi strategies but they also should make a specific competitive program as an effort to reach students candidate in choosing the institution as a place to study. The study recommends that the administrators of institution make a comprehensive digital marketing to enable them an optimal selling. Keywords Private Islamic Higher Education, Education Marketing Strategy, Competitive higher education